Perspektif Ontologis dan Epistemologis Model Project Based Learning dalam Filsafat Pendidikan Matematika - Annafi Awantagusnik (JURNAL ARMADA PENDIDIKAN, 2025)
Kurikulum Merdeka makes it possible to achieve equal distribution of knowledge obtained by students because it is adapted to the potential and needs of students. Project Based Learning (PjBL) is one of the learning models recommended by Kurikulum Merdeka to be applied in learning, one of which is in learning mathematics. PjBL provides experience and knowledge to students through project creation activities. This is able to encourage students to construct their own knowledge after the presentation of project results is complete, which will involve reducing some information that may not be needed. PjBL can be viewed from the philosophy of mathematics education. The type of this research is descriptive research and literature study (library research).The aim of this research is to describe the PjBL model as seen from the philosophy of mathematics, namely from the branches of ontology and epistemology. This article was written based on a literature search based on writings that discuss the philosophy of mathematics education in terms of ontology and epistemology. Judging from the ontology of mathematics education philosophy, this is in accordance with the flow of empiricism and logicism. Meanwhile, in terms of epistemology, the philosophy of mathematics education is in line with constructivism, which means that knowledge is produced from a construction process by students